The Study of Lexical and Contextual Meaning on Lily Song By Alan Walker Feat K-391 & Emelie Hollow (Semantic Approach) - Asrifan, Andi; Vargheese, K. J.; Hasnidar, Hasnidar; Hermasyah, Sam; Suleha, Suleha (Study Program of English Literature, 2021)
Abstract. The aim this article is study about semantic. Semantic is the branches of linguistics which systematically study about meaning. This branch is the important one, and there are lexical meaning and contextual meaning. By listening to the songs, we can get the message of the song. Therefore, the researcher was interested in analyzing the kinds of meaning used on the lyric of Lily Song by Alan Walker Feat K-391 & Emelie Hollow. The researcher dedicated to give the title of this research â€œThe Study of Lexical and Contextual Meaning on Lily Song by Alan Walker Feat K-391 & Emelie Hollow (Semantic Approach)â€.This study uses a descriptive qualitative method because the researcher would identify and interpret the research object of Lily Song. The step to obtain the data is by collecting sources of the data from Lily Song Lyrics and from internet. After that she selects the songs which contain of semantic, reads and listens to the lyrics to understand the content of the songs conducts and analyzes the collected data and makes conclusion. The result of this research is as follows: (1) related to the lexical meaning, while (2) related to the contextual meaning. The reseracher expects this research will be useful for the other researchers who are eager to know more about semantics. Moreover, semantic is an important branch of linguistics that is interesting to be studied, especially when it is applied to literary works, such us songs or poem etc. Keywords: Semantic, lexical meaning, contextual meaning, song